2021
DOI: 10.1136/bmjopen-2021-052221
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional assessment of tuberculosis and HIV prevalence in 13 correctional facilities in Zambia

Abstract: ObjectiveTo determine the prevalence of tuberculosis (TB) and HIV in 13 Zambian correctional facilities.MethodsCross-sectional study.Setting13 correctional facilities in seven of the 10 provinces in Zambia.ParticipantsAll incarcerated individuals were eligible for TB and HIV screening and testing. Of the total study population of 9695 individuals, which represent 46.2% of total correctional population at the beginning of the study, 8267 and 8160 were screened for TB and HIV, respectively.InterventionsTB and HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…incarcerated at any given time. 2 HIV prevalence in this population is estimated to range from 14.3% to 27.4%, [3][4][5][6][7] rates that are considerably higher than that seen in the general population. 8 There is increasing recognition that to achieve the "95-95-95" goals set by the Joint United Nations Programme on HIV/AIDS for 2030, 9 greater attention must be given to ensuring high levels of HIV testing, antiretroviral therapy (ART) initiation, and treatment maintenance among incarcerated and other key populations.…”
mentioning
confidence: 88%
“…incarcerated at any given time. 2 HIV prevalence in this population is estimated to range from 14.3% to 27.4%, [3][4][5][6][7] rates that are considerably higher than that seen in the general population. 8 There is increasing recognition that to achieve the "95-95-95" goals set by the Joint United Nations Programme on HIV/AIDS for 2030, 9 greater attention must be given to ensuring high levels of HIV testing, antiretroviral therapy (ART) initiation, and treatment maintenance among incarcerated and other key populations.…”
mentioning
confidence: 88%
“…Six studies assessed interventions involving screening campaigns that estimated the prevalence of HIV in prisons across different countries. 8,17,24,26,34,36 On the one hand, the studies suggest weak HIV infection control practices in SSA prisons in terms of screening at entry, during incarceration, and at exit from prison. This is reflected in the low proportion of inmates who knew their HIV status prior to screening.…”
Section: Screening For Hivmentioning
confidence: 99%
“…The most common approach reported in these studies involved mass screening of inmates, with findings indicating a higher prevalence of HIV in prison settings compared to national estimates. 17,24,26,34,36 For example, Maggard et al, reported an HIV prevalence of 22.9% during a mass screening of inmates in six prison facilities in Zambia. 34 In another screening campaign in five South African correctional facilities, Stevenson et al found an estimated HIV prevalence of 17.7% with most (73.4%) being previously undiagnosed.…”
Section: Screening For Hivmentioning
confidence: 99%
See 1 more Smart Citation
“…There are an estimated 26,840 people who inject drugs (PWID), with an HIV prevalence of 24% [ 8 ]. Over 22,000 people are incarcerated, with HIV prevalence estimates ranging from 14% to 27% [ 16 , 17 , 18 ]. Overall, KPs face high HIV prevalence resulting from complex determinants of transmission risk, including structural and individual factors [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%